Diseño de un sistma de calentamiento de agua sanitaria(ACS) Híbrido: una alternatIva para el edificio Centauro en la ciudad de Latacunga. - Terán Herrera, Héctor Cochise (2013)
In this paper a theoretical study of the field of solar collection is performed in the city of Latacunga, in order to be exploited in the heating of domestic hot water (DHW) proposing an efficient alternative to solar energy thereby reducing consumption LPG and CO2 emissions to the atmosphere. The literature review highlights the scope of the work performed in methodologies for characterizing the DHW system and energy analysis, technical data reflecting economic utility for the proposed hybrid system. It is part of the characterization of the DHW system where energy carriers is analyzed, from there a comparison with preliminary data recorded at least Ecuadorian and international standards, with the aim of contributing to solutions related to the economic impact is made, negative environmental and human health, the most significant impact of energy losses through system simulation of domestic water heating in SHUCO CHART AND TRANSOL program, where the system is analyzed for a full year are analyzed volume ratios , overheating, resulting in a system installation of solar water heating support DHW with GLP energy.